Risk Factors and Adverse Drug Reactions in HIV/AIDS Patients at Undata Regional Hospital in Palu City, Indonesia (Sciences of Pharmacy, 2023)
AIDS (acquired immunodeficiency syndrome) is a clinical manifestation of the late stage of HIV infection (human immunodeficiency virus). This virus attacks CD4 cells in the immune system which is an important component in fighting infection. Without treatment, HIV can gradually destroy the immune system and lead to AIDS. This study aims to identify risk factors and determine and identify the type of ADR in HIV/AIDS patients at Undata Regional General Hospital Palu, Central Sulawesi province. This study used a cross-sectional observation method with prospective data collection, with a sample of 126 patients. Based on the results of the study, patients with HIV/AIDS had the most risk factors, namely homosexuality as many as 73 patients (58%), at the clinical stage, namely stage 3, 50 patients (39%), on opportunistic infection data, namely candidiasis, 35 patients (33%), and the initial CD4 cell count of <200 cells/mm3 in 27 patients (21%). Patients with HIV/AIDS who experienced ADR using antiretroviral drugs were 255 out of a total of 126 patients. Types of ADR that occur in HIV/AIDS patients include fever (6%), dizziness (47%), nausea (12%), vomiting (7%), insomnia (15%), easy hunger (1%), Hb low (1%), weakness (1%), rash (9%), headache (1%). Overall, these findings contribute valuable information for developing targeted interventions and improving the overall care and outcomes for individuals with HIV/AIDS.